Intellectual property as a factor of national security of Ukraine - Schimpf, Karin; Pererva, P. G. (My University, 2022)
It is proved that special attention should be paid to the development of intellectual property management strategy at all stages of its creation and development. In the absence of legal protection of objects of exclusive rights, which by law excludes the possibility of illegal reproduction or use by third parties of the same object, developers are unlikely to have an incentive to create and develop their creations.
Інтелектуальна власність як фактор національної безпеки України
Keywords: intellectual property; exclusive right; author; right holder; offense